2015
DOI: 10.18632/oncotarget.3754
|View full text |Cite
|
Sign up to set email alerts
|

MiR-744 functions as a proto-oncogene in nasopharyngeal carcinoma progression and metastasis via transcriptional control of ARHGAP5

Abstract: Nasopharyngeal carcinoma (NPC) is a highly invasive and metastasis-prone epithelial cancer. The paucity of effective treatment strategies for recurrent and metastatic NPC is the major cause for stagnating survival rate of NPC. Therefore, it's urgent to understand the molecular mechanisms underlying NPC progression and identify novel avenues for targeted therapy. It has emerged recently that microRNAs are potential pro-tumorigenic or tumor-suppressive factors that participate in oncogenesis. In this study, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…miR-744 upregulation inhibits cell proliferation and promotes cell cycle arrest in hepatocellular carcinoma (31). On the contrary, miR-744 serves oncogenic roles in prostate cancer (28), laryngeal squamous cell carcinoma (29), pancreatic cancer (27) and nasopharyngeal carcinoma (32). These findings indicate that the biological roles of miR-744 exhibit tissue specificity in tumorigenesis and tumour development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…miR-744 upregulation inhibits cell proliferation and promotes cell cycle arrest in hepatocellular carcinoma (31). On the contrary, miR-744 serves oncogenic roles in prostate cancer (28), laryngeal squamous cell carcinoma (29), pancreatic cancer (27) and nasopharyngeal carcinoma (32). These findings indicate that the biological roles of miR-744 exhibit tissue specificity in tumorigenesis and tumour development.…”
Section: Discussionmentioning
confidence: 98%
“…miRNAs serve crucial roles in the regulation of their target genes (33). Numerous human genes, including Notch1 (17), B-cell lymphoma 2 (18), secreted frizzled-related protein 1 precursor (27), glycogen synthase kinase 3β (27), transducing like enhancer of split 2 (27), naked cuticle homolog 1 (28), programmed cell death 4 (29), phosphatase and tensin homolog (29), c-myc (31) and Rho GTPase activating protein 5 (32), have been identified as direct miR-744 targets. In the present study, NOB1 was predicted as a direct target gene of miR-744 in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR‐497 was found to inhibit NPC cell proliferation and migration in vitro and xenograft tumor growth in vivo . miR‐744 shows the ability to promote NPC growth and metastasis . These studies pinpoint the importance of miRNAs in the pathogenesis of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐744‐3p has been shown to regulate tumor development and growth in cell line by inducing cyclin B1 expression and functioned as a tumor promoter in nasopharyngeal carcinoma . Previous microarray studies have identified that miR‐744‐3p was up‐regulated in psoriasis .…”
Section: Introductionmentioning
confidence: 99%